Determinant Of Fraud Prevention In Regional Financial And Asset Management: Moderation Of Internal Audit - Rosari, Renya; Utomo, Dwi Cahyo (LPPM ISNJ Bengkalis, 2024)
This research aims to find empirical evidence of the influence of the internal control system, auditor competence, and organizational culture on fraud prevention, with internal audit as a moderating variable. This study applied a quantitative method and a causally associative approach. Employees at the Financial and Asset Management Agency of Kupang Regency and City Government were population in this study 91 civil servants. The sample was chosen using purposive sampling, and the research sample was 75 respondents. Data collection uses survey techniques by distributing questionnaires to be filled out by employees. Partial least squares-structural equation modelling (PLS-SEM) is used in the data analysis with SmartPLS version 3.29. The result of this study indicates that internal control systems, auditor competence, and organizational culture positively affect fraud prevention. Internal audits do not affect fraud prevention. Internal audit can moderate the effect of internal system control and auditor competence. Internal audits cannot moderate the relationship between organizational culture and fraud prevention. This research can contribute to advancing current theory and be a reference for further research, especially on fraud risk. This research can be a reference for audit institutions in advancing best practices to improve the effectiveness of government audits in reducing and preventing fraud.